First description of the neuro‐anatomy of a larval coral reef fish Amphiprion ocellaris. Issue 3 (26th June 2016) - Jacob, H.; Metian, M.; Brooker, R. M.; Duran, E.; Nakamura, N.; Roux, N.; Masanet, P.; Soulat, O.; Lecchini, D.
Abstract : The present study described the neuro‐anatomy of a larval coral reef fish Amphiprion ocellaris and hypothesized that morphological changes during the transition from the oceanic environment to a reef environment ( i.e. recruitment) have the potential to be driven by changes to environmental conditions and associated changes to cognitive requirements. Quantitative comparisons were made of the relative development of three specific brain areas (telencephalon, mesencephalon and cerebellum) between 6 days post‐hatch (dph) larvae (oceanic phase) and 11 dph (at reef recruitment). The results showed that 6 dph larvae had at least two larger structures (telencephalon and mesencephalon) than 11 dph larvae, while the size of cerebellum remained identical. These results suggest that the structure and organization of the brain may reflect the cognitive demands at every stage of development. This study initiates analysis of the relationship between behavioural ecology and neuroscience in coral reef fishes.